STUDENTS’ PERCEPTIONS AND ATTITUDES TOWARDS THE USE OF WHATSAPP IN EFL CLASSES IN BENINESE NATIONAL UNIVERSITIES - EGOUNLETI, Pédro Marius (My University, 2021)
In 21st century, technology has become an integral part of our daily life including the educational system. The current spread of the internet and its diverse applications have yielded many benefits especially, the use of web-based technologies in education. Over the recent months, the number of universities and students using these technologies has drastically increased worldwide after the outbreak of COVID 19. This study examines Beninese EFL students’ perceptions and attitudes towards the use of WhatsApp in their EFL classes. The participants are 45 students including 30 males and 15 females during the academic year 2021-2022 from the technical college of Abomey Calavi University in the Benin Republic. In order to achieve the objectives of the study, a mixed research method is employed using multiple tools for data collection including a questionnaire, a focus group and phone interview via WhatsApp. The analysis of the data reveals that the participating EFL students have positive perceptions and attitudes towards the use of WhatsApp in EFL classes. Moreover, the students involved in the present study use WhatsApp applications to send and receive different learning materials and activities for communicating with instructors and among themselves. In the light of these results, the present investigation encourages faculty members to integrate social media into the teaching environments by providing them with a training program, workshops and online trainings. In addition, the need to provide faculty members with curricular plans and activities requires the implementation of WhatsApp in the learning environments.
Keywords: EFL Students- WhatsApp-Perceptions-Attitudes-Classes.